Dense cold‐water coral garden of Paragorgia johnsoni suggests the importance of the Mid‐Atlantic Ridge for deep‐sea biodiversity. Issue 23 (24th November 2021) - Morato, Telmo; Dominguez‐Carrió, Carlos; Mohn, Christian; Ocaña Vicente, Oscar; Ramos, Manuela; Rodrigues, Luís; Sampaio, Íris; Taranto, Gerald H.; Fauconnet, Laurence; Tojeira, Inês; Gonçalves, Emanuel J.; Carreiro‐Silva, Marina
Abstract: Mid‐ocean ridges generate a myriad of physical oceanographic processes that favor the supply of food and nutrients to suspension‐ and filter‐feeding organisms, such as cold‐water corals and deep‐sea sponges. However, the pioneering work conducted along the Mid‐Atlantic Ridge failed to report the presence of large and dense living coral reefs, coral gardens, or sponge aggregations. Here, we describe the densest, near‐natural, and novel octocoral garden composed of large red and white colonies of Paragorgia johnsoni Gray, 1862 discovered at 545–595 m depth on the slopes of the Mid‐Atlantic Ridge, in the Azores region. This newly discovered octocoral garden is a good candidate for protection since it fits many of the FAO criteria that define what constitutes a Vulnerable Marine Ecosystem. The observations described here corroborate the existence of a close relationship between the octocoral structure and the ambient currents on ridge‐like topographies, providing new insights into the functioning of mid‐ocean ridges' ecosystems. The ubiquitous presence of biogenic and geological topographies associated with mid‐ocean ridges, which could act as climate refugia, suggests their global importance for deep‐sea biodiversity. A better understanding of the processes involved is, therefore, required. Our observations may inspire future deep‐sea research initiatives to narrow existing knowledge gaps of biophysical connections with benthic fauna at small spatial scales along mid‐ocean ridges. Abstract : This manuscript describes the most dense, near‐natural, and novel octocoral garden composed of large red and white colonies of bubblegum corals ( Paragorgia johnsoni Gray, 1862), discovered on the slopes of a small ridge‐like structure located on the Mid‐Atlantic Ridge, in the Azores region. The observations described here suggest a close relationship between the octocoral structure and the ambient currents on ridge‐like topographies providing new insights into the functioning of mid‐ocean ridges. The ubiquitous presence of biogenic and geological topographies associated with mid‐ocean ridges suggests their global importance for deep‐sea biodiversity and as climate refugia.